2011
DOI: 10.1371/journal.pone.0025669
|View full text |Cite
|
Sign up to set email alerts
|

Cardiosphere-Derived Cells Improve Function in the Infarcted Rat Heart for at Least 16 Weeks – an MRI Study

Abstract: AimsEndogenous cardiac progenitor cells, expanded from explants via cardiosphere formation, present a promising cell source to prevent heart failure following myocardial infarction. Here we used cine-magnetic resonance imaging (MRI) to track administered cardiosphere-derived cells (CDCs) and to measure changes in cardiac function over four months in the infarcted rat heart.Methods and ResultsCDCs, cultured from neonatal rat heart, comprised a heterogeneous population including cells expressing the mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 32 publications
(52 reference statements)
2
60
0
3
Order By: Relevance
“…Early trials of cardiac repair and regeneration via transplantation of bone marrow-derived stem/progenitor cells have given mixed and modest results (for review see 37 ), indicating that a better understanding of the relevant cell biology is required to provide a consistently effective therapeutic option for stem cell-based regenerative treatments in the heart. The presence of resident eCSCs in the adult heart, including human, has been determined by several groups 2,4,6,[8][9][10]12,14,17,[38][39][40][41][42] . These cells can be isolated and propagated in vitro to produce large numbers of cells without reaching growth arrest or their being a change in cell characteristic.…”
Section: Characterisation Of Ecscsmentioning
confidence: 99%
“…Early trials of cardiac repair and regeneration via transplantation of bone marrow-derived stem/progenitor cells have given mixed and modest results (for review see 37 ), indicating that a better understanding of the relevant cell biology is required to provide a consistently effective therapeutic option for stem cell-based regenerative treatments in the heart. The presence of resident eCSCs in the adult heart, including human, has been determined by several groups 2,4,6,[8][9][10]12,14,17,[38][39][40][41][42] . These cells can be isolated and propagated in vitro to produce large numbers of cells without reaching growth arrest or their being a change in cell characteristic.…”
Section: Characterisation Of Ecscsmentioning
confidence: 99%
“…These data suggest that there may be improvements in certain measures of heart function with H 2 O 2 preconditioned CPCs, specifically those related to diastolic contractility/ relaxation, but these did not translate to global changes in the ejection fraction. While this may initially seem confusing, some prior studies have demonstrated that changes in function may be more apparent at longer time points [33][34][35]. Moreover, the fact that H 2 O 2 preconditioned CPCs are not generating large amounts of new myocytes may also contribute to this phenomenon.…”
Section: Fig 4 H 2 O 2 Preconditionedmentioning
confidence: 99%
“…Several studies have been carried out to isolate and characterize cardiac precursor cells (mainly c-Kit + , Sca-1 + , and cardiospheres) from normal and pathologic fetal and adult heart biopsies [12][13][14][15]. Different protocols have been developed to improve CSC isolation methods, resulting in the generation of a specific population of CSCs [16][17][18][19]. In addition to cell sorting and culture of explants, clonogenic expansion of cells has been described as another CSCs isolation method [20].…”
mentioning
confidence: 99%